The longitudinal progression of autonomic dysfunction in Parkinson's disease: A 7-year study - Stewart, Charlotte B.; Ledingham, David; Foster, Victoria K.; Anderson, Kirstie N.; Sathyanarayana, Sahana; Galley, Debra; Pavese, Nicola; Pasquini, Jacopo (Frontiers in Neurology, 2023)
Background: Autonomic dysfunction, including gastrointestinal, cardiovascular and urinary dysfunction, is often present in early Parkinson’s Disease (PD). Knowledge of the longitudinal progression of these symptoms, and the relationship between different autonomic domains, is limited. Furthermore, whether the presence of autonomic symptoms in early-stage PD correlates with olfactory dysfunction, a possible marker of central nervous system involvement, has not been fully investigated. Objectives: We aimed to investigate the occurrence and progression of autonomic dysfunction in PD and determine any coexistence of symptoms in individual patients. We also investigated the relationship between autonomic symptoms, olfactory dysfunction, and motor impairment. Methods: Data were obtained from the Parkinson’s Progression Markers Initiative (PPMI) database. Autonomic dysfunction was measured using the Scales for Outcomes in Parkinson’s Disease (SCOPA-AUT). Symptom frequency and mean scores over seven years was determined. The simultaneous occurrence of autonomic symptoms was also examined. Finally, the relationship between SCOPA-AUT scores, olfactory dysfunction, and motor impairment were investigated using the University of Pennsylvania Smell Identification Test (UPSIT) and the Movement Disorder Society – Unified Parkinson’s Disease Rating Scale (MDS-UPDRS), respectively. Results: Seven years of follow-up data was available for 171 patients and 136 controls. Mean SCOPA-AUT score increased significantly from baseline to the seven-year follow-up for each autonomic domain, except for female sexual dysfunction. There was a high percentage of PD patients and controls reporting urinary dysfunction (> 90%). Most patients reported more than three autonomic symptoms, with clustering of symptoms increasing over the seven-year period. Common clusters of dysfunction were composed of gastrointestinal, urinary, thermoregulatory and sexual dysfunction. At baseline, SCOPA-AUT total score showed an inverse association with UPSIT scores (r = -0.209, p = 0.006). Conclusions: SCOPA-AUT increased over time, with most patients reporting gastrointestinal and urinary symptoms. Additionally, autonomic manifestations coexist in PD, with increasing number of symptoms experienced with PD progression. Urinary, gastrointestinal, thermoregulatory and sexual dysfunction were found to cluster together. An inverse association between SCOPA-AUT scores and UPSIT scores was found at baseline, indicating overall greater olfactory impairment in participants with higher SCOPA-AUT scores.